Manajemen Sumber Daya Manusia Untuk Meningkatkan Mutu Pendidikan: Perspektif Total Quality Management - Qory, Ananda Leila; Sitti Chadidjah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Various efforts to improve the quality of education have often not produced significant changes, even in the midst of higher demands for quality and competitiveness. This condition shows that the problem of education quality is not only in the curriculum or infrastructure, but also in the weak management of educational human resources which is the main driver of the education system. This article aims to examine human resource management in improving the quality of education from the perspective of the Total Quality Management (TQM) theory, with an emphasis on the thought of W. Edwards Deming This research uses the library research method (library research) through book review, scientific journal articles, and relevant previous research results. The data was analyzed descriptively-analytically to obtain an in-depth picture of the implementation of TQM principles in the management of educational human resources. The results of the study show that the implementation of TQM can be a strategic solution in improving the quality of education through continuous improvement, the implementation of the Plan-Do-Check-Act (PDCA) cycle, visionary and participatory leadership, strengthening teamwork, and the continuous development of the competence of educators and educational personnel. In addition, TQM-based human resource management plays an important role in building a quality culture and increasing the satisfaction of education customers. Thus, human resource management in the perspective of Total Quality Management is not only theoretically relevant, but also a strategic and applicative approach in answering the challenge of improving the quality of education in a sustainable way.